2017
DOI: 10.1016/j.humpath.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid- β –related angiitis: a report of 2 cases with unusual presentations

Abstract: Amyloid-β-related angiitis (ABRA) is a rare complication of cerebral amyloid angiopathy in which amyloid-β deposition in the leptomeningeal and cortical vessels is associated with vasculitis characterized by transmural lymphohistiocytic, often granulomatous, inflammation. Patients usually present with acute to subacute cognitive dysfunction, headaches, and focal neurologic deficits. We report 2 cases of ABRA with unusual clinical presentations, including one case with fatal cerebral edema leading to herniation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Based on histopathology of brain biopsy, two forms of CAA-ri can be distinguished: inflammatory CAA (ICAA) and Amyloid-β-Related Angiitis (ABRA). Specifically, while ICAA is characterized by a perivascular inflammation, ABRA is characterized by transmural and intramural inflammation, often with granulomas formation (Moussaddy et al, 2015;Ng et al, 2017;Chu et al, 2016). ICAA and ABRA share several clinical and neuroradiological features and are indistinguishable from each other without histopathological data (Salvarani et al, 2016;Chu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on histopathology of brain biopsy, two forms of CAA-ri can be distinguished: inflammatory CAA (ICAA) and Amyloid-β-Related Angiitis (ABRA). Specifically, while ICAA is characterized by a perivascular inflammation, ABRA is characterized by transmural and intramural inflammation, often with granulomas formation (Moussaddy et al, 2015;Ng et al, 2017;Chu et al, 2016). ICAA and ABRA share several clinical and neuroradiological features and are indistinguishable from each other without histopathological data (Salvarani et al, 2016;Chu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although a validation of cut-offs has not yet been performed, previous studies reported significantly higher values of CSF anti-Aβ antibodies in subjects affected by CAA-ri compared to control subjects (Piazza et al, 2013), just as in our cases. Therefore, the research of anti-Aβ antibodies not only focuses on the possible pathogenic mechanism of the disease but also represents a possible useful biomarker for the diagnosis and non-invasive monitoring of CAA-ri (DiFrancesco et al, 2011;Moussaddy et al, 2015;Ng et al, 2017;Salvarani et al, 2016;Chu et al, 2016;Charidimou, 2016;Sakaguchi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 17 It is worth mentioning that Amyloid b-related angiitis, caused by amyloid-b peptide deposition in the brain leading to vessel wall breakdown, is a subset of PACNS but patients tend to present the condition at an older age. 18 The histological differential diagnosis of PACNS includes sarcoidosis and infectious meningitides, but these have distinctive patterns such as viral inclusions, neuronophagia, parenchymal inflammation, and/or demyelination and are not restricted to blood vessels. The angiocentric accumulation of lymphoid cells may also bear a superficial resemblance to primary CNS lymphoma, especially well-differentiated lymphoplasmacytoid variants, but infiltrates of neoplastic cells tend to be more extensive, may be partly necrotic, contain much more reticulin, lack a granulomatous component, and have a characteristic immunophenotype.…”
Section: Usefulness Of Brain Biopsies To Diagnose Cognitive Impairmenmentioning
confidence: 99%
“…Cerebral amyloid angiopathy-related inflammation (CAA-ri) is a rare disorder of the central nervous system (CNS) that arises from development of autoantibodies to amyloid-beta protein (Aβ) within the walls of the leptomeningeal and cortical blood vessels (15). It affects immunocompetent individuals who present with non-specific symptoms or focal neurological deficits, which typically elicits a broad etiological investigation until the condition is recognized (68). The presumptive diagnosis is based on clinical and neuroimaging data, whereas the definitive diagnosis is histological (9).…”
Section: Introductionmentioning
confidence: 99%